Case reportThe diagnostic difficulties of pemphigus vegetans – a case report - Karlińska, Marlena; Waszczykowska, Elżbieta; Torzecka, Jolanta Dorota (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Pemphigus vulgaris as an intra-epidermal autoimmune blistering disorder is characterized by the presence of autoantibodies against desmoglein. Pemphigus vegetans is a rare type of pemphigus vulgaris, which occurs in 1-2% of all cases. We describe a 60-year-old woman with pemphigus vegetans with atypical clinical symptoms at the beginning of the disease which caused a delay in establishment of diagnosis and the introduction of appropriate treatment.